PENGARUH PEMBELAJARAN IPA BERBASIS SETS (Science, Environment, Technology and Society) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD - Muh. Alimin Agus; Khaeruddin Khaeruddin; Evi Ristiana (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine whether there is an effect of critical thinking skills and students' science learning outcomes after participating in SETS-based science learning. This research is a quantitative research. The type of research used is a quasi experimental design. The population in this study were all students of SDN 70 Manjalling, Maros Regency with a total of 354 students and the research sample was class V students of SDN 70 Manjalling which consisted of 2 groups in class VA totaling 25 people and class VB totaling 24 people. Data collection techniques in this study were carried out using test techniques to determine critical thinking skills in the form of 6-item essay questions and science learning outcomes in the form of 20 multiple-choice questions. The results of the study based on descriptive analysis showed that (1) The average critical thinking ability of SETS-based science learning was 88.12 and direct learning (conventional) was 80.54. This means that SETS-based science learning is better than conventional learning. This means that SETS-based science learning is better than conventional learning. While the results of the inferential analysis showed that SETS-based science learning had a more significant effect on the critical thinking skills of fifth grade students at SDN 70 Manjalling, Kabupaten Maros. This is based on the multivariate test table in the manova test, the Sig value is obtained. 0.001 < 0.05